Kinematics analysis of volleyball Open Spike in the elite athletes - Irawan, F. A.; Permana, D. F. W.; Hadi, H.; Romadhoni, S. (Proceedings of the 6th International Seminar on Public Health and Education, ISPHE 2022, 29 June 2022, Semarang, Central Java, Indonesia, 2023)
Abstract. The aim of this study was to analyse the Open Spike motion in volleyball in the implementation of elite athletes perform in Semarang. This study used analytical research with One Short Case Design. This study was conducted at the Semarang volleyball association with 11 participants and all sample were agreed to participated in this study with full fill the inform consent. Study analysis using a video analysis software Dartfish version 8 and then processed to find kinematics data. This study found that Open Spike Volleyball in Semarang elite athletes is in a good category. The data showed that the average of the open spike time was 1.01 second and impact was 0.57 second. These results stated that open spike in this study was in the category quite appropriate the biomechanics aspect. The limitation in this study was only measure the kinematics data, and for future research, hopefully future research measure kinetics data on the arm power and leg power to the open spike.